Prevalence and Association Between Occupational Noise Exposure and Hearing Loss Among Workers in Indonesia - Ritwan Agus Prasetyo; Abdul Rohim Tualeka; Juliana Jalaludin (Universitas Airlangga, 2026)
Background: Hearing loss is one of the health problems among Indonesian workers, with one of the cause being uncontrolled noise exposure. Noise levels in each region of Indonesia vary depending on the number and type of industries in the area. This situation increases the risk of Noise-Induced Hearing Loss (NIHL), especially among productive workers aged 15–49 who are continuously exposed to noise. Objectives: This study aims to describe the prevalence and analyze the association between noise exposure and hearing loss among workers aged 15–49 years using Global Burden of Disease (GBD) data. Methods: This study employed a descriptive analysis design using Disability-Adjusted Life Years (DALYs) and Summary Exposure Value (SEV) data from 32 provinces. Regression analysis was conducted to assess the association between noise exposure and the burden of hearing loss. Results: The study results showed that noise levels and disease burden varied across provinces. The Summary Exposure Value (SEV) for highest noise exposure was observed in Yogyakarta (9.40), followed by North Sulawesi (9.17), and Bali (9.15). The highest Disability-Adjusted Life Years (DALYs) were recorded in West Java (109,204.28 per 100,000 population), followed by East Java (85,966.51 per 100,000 population), and Central Java (79,062.85 per 100,000 population). Regression analysis indicated a weak association between noise and hearing loss (R²=0.179). Conclusion: Noise levels in Indonesia vary across provinces, with Yogyakarta, North Sulawesi, and Bali showing the highest levels. This variation is influenced by the type and number of vehicles, noise intensity, and other contributing factors. West Java, East Java, and Central Java have the highest disease burden. However, the weak association between noise exposure and disease burden suggests that hearing loss is not solely caused by noise exposure.